Body donor reperfusion and re-ventilation in medical training: an Italian study testing SimLife® - Irene Neri; Giulio Vara; Antonietta Fazio; Maria Vittoria Marvi; Foteini-Dionysia Koufi; Elisa Boschetti; Simone Lodi; Giulia Adalgisa Mariani; Marilisa Quaranta; Anna Maria Billi; Alessandra Ruggeri; Carlo Barausse; et al. (Frontiers in Medicine)
BackgroundMedical simulations have emerged as a valuable tool in anatomical-medical training, allowing healthcare professionals to gain hands-on experience in a controlled and safe environment. One such simulation platform is SimLife®, which uses the Pulse for Practice (P4P) system to enable realistic restoration of airflow (“re-ventilation”) and blood flow (“revascularization”) in bodies donated to science.ObjectiveThis study aimed to evaluate the feasibility of introducing SimLife® technology in Italy. Additionally, it assessed the impact of this technology across various medical specialties, utilizing a minimal number of donated bodies.MethodsThe study utilized the existing body donation program and dissection rooms at the Anatomy Center of the University of Bologna. 62 participants from 13 medical specialties performed simulations using the SimLife® P4P platform. Post-simulation, structured interviews were used to collect data on the interventions performed, participant perceptions of the technology’s usefulness, enjoyment, and willingness to repeat the experience, as well as critical issues encountered.ResultsKey findings include that 86% of participants rated SimLife® technology as extremely useful for post-lauream training, while 84% found it highly beneficial for team-building activities. A total of 31 interventions were successfully performed across various anatomical regions, with participants reporting high satisfaction and a strong willingness to repeat the simulation experience.ConclusionThe findings support the effectiveness of SimLife® technology for body donor re-ventilation and revascularization, reinforcing its value for medical training across various specialties.